The Fifth Coefficient Approximation of The Inverse Strongly Convex Function - Krisna Adilia Daniswara; Aris Alfan; Ahmad Khairul Umam (Jurnal Matematika Sains dan Teknologi, 2023)
This paper discusses the fifth coefficient approximation of the inverse strongly convex function. Strongly convex function is a subclass of convex function. Those functions are included as univalent functions. Using corresponding lemmas, we give sharp limits for the fifth coefficient of the inverse strongly convex function. The limit is sharp if the value of the approximation has the same value as the limit. We verify that the limit of the fifth coefficient of the inverse strongly convex function differs from that of the strongly convex function in some interval but still have the same value in a point. Besides, we also explain that the sharp limit of the fifth inverse coefficient is less than or equal to one.